Implementation of Building Information Modeling in Quantity Take-Off of Construction Projects - Junita Eka Susanti; Muhammad Azka Abdullah; Putri Ayu Dwiyana (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2026)
Building Information Modeling (BIM) is one of the mothods that has been rapidly developing in the Architecture, Engineering, and Construction (AEC) industry. This study aims to implement the concept of BIM using Autodesk Revit in the processess of structural modeling, volume estimation through Quantity Take – Off, and structural Clash Detection analysis in the modeling of Hospital Medical Building. The research employs a descriptie quantitative approach, explaining the modeling stages and volume calculations based on data obtained from Autodesk Revit. The modeling process was carried out in an integrated manner, producing a 3D model and 2D construction drawings in accordance with the technical project data provided in the appendices. The Quantity Take – Off results for structural elements are as follow: foundations structure of 837.693 m3, structural wall retaining wall of 79.402 m3, column structure of 708.710 m3, framing beam structure before clash detection of 1095.523 m3, floor slab structure of 737.004 m3, and BJTS reinforcement structure before clash detection of 97.469 m3, with a total rebar weight of 843.418 tons (rounded to 844 tons). The clash detection process using the Interference Check feature in Autodesk Revit assisted in resolving conflicts within the model and enhanced the accuracy of the quantitative data. The resulting QTO volumes after clash detection were: framing beam structure of 1095.549 m3 with a ratio of 0.002%, and BJTS reinforcement of 97.478 m3 with a ratio of 0.010% with rebar weight of 843.492 Tons (a difference of 0.009%).